PENGALIHAN BENDA ELEKTRONIK DARI DEBITUR KE PIHAK KETIGA TANPA SEPENGETAHUAN KREDITUR - Hermiani Ariano (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT  Transfer of Electronic Items From Debtors To Third Parties Unbeknownst to Creditors Guided by Drs. H. Irman Syahrial, SH., M.Hum as the supervisor of I and Mia Kusuma, SH., M.Hum as mentorsII.This study aims to determine the legal consequences if the debtor performs the transfer of electronic objects from the debtor to a third party without the knowledge of the creditor and legal protection for the creditor against the transfer of electronic objects from the debtor to a third party without the knowledge of the creditor.Research conducted by the author on "Transfer of Electronic Items From Debtors To Third Party Without Creditor's Knowledge" then the authors do research through the existing literature, especially legislation related to the material from the writing of the thesis, as well as research keperpustakaan and take the case From the internet / website that has the verdict.The results showed that the transfer of an object in the Transfer of Electronic Items From Debtors To Third Parties Without the knowledge of Creditors is still a lot happening. There are still some cases of diversion of an object, generally caused by the intention / intention of the debtor to make the transfer. Then the legal consequences if the debtor performs the transfer of electronic objects without the knowledge of the creditor that is with the prison law for 4 (four) years and or by paying a fine of Rp. 50,000,000. While the legal protection for creditors against the transfer of electronic objects from debtors to third parties without the knowledge of creditors by making agreements on paper that use matrai, report to the police (police), and insure the electronic object.Keywords: Electronic Material Transfer.